Pulmonary hypertension and vasculopathy in incontinentia pigmenti: a case report - Alshenqiti A; Nashabat M; AlGhoraibi H; Tamimi O; Alfadhel M (Dove Medical Press, 2017)
Abduljabbar Alshenqiti,1 Marwan Nashabat,1 Hissah AlGhoraibi,1 Omar Tamimi,2 Majid Alfadhel1 1Division of Genetics, Department of Pediatrics, King Abdullah International Medical Research Centre, King Saud bin Abdulaziz Uiversity for Health Sciences, King Abdulaziz Medical City, Ministry of National Guard Health Affairs (NGHA), Riyadh, Saudi Arabia; 2Department of Cardiology, King Abdullah International Medical Research Centre, King Saud bin Abdulaziz University for Health Sciences, King Abdulaziz Medical City, Ministry of National Guard-Health Affairs (NGHA), Riyadh, Saudi Arabia Abstract: Incontinentia pigmenti (IP; Bloch–Sulzberger syndrome) is a rare, genetic syndrome inherited as an X-linked dominant trait. It primarily affects female infants and is lethal in the majority of males during fetal life. The clinical findings include skin lesions, developmental defects, and defects of the eyes, teeth, skeletal system, and central nervous system. Cardiovascular complications of this disease in general, and pulmonary hypertension in particular, are extremely rare. This report describes the case of a 3-year-old girl with IP complicated by pulmonary arterial hypertension. Extensive cardiology workup done to the patient indicates underlying vasculopathy. This report sheds light on the relationship between IP and pulmonary hypertension, reviews the previously reported cases, and compares them with the reported case. Keywords: incontinentia pigmenti, IKBKG, pulmonary hypertension, vasculopathy, Bloch–Sulzberger syndrome, lines of Blaschko, hyperpigmentation